2011
DOI: 10.1021/jp206940j
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Protein-Imprinted Polymers. 3. Imprinting Selectivity

Abstract: Molecular imprinting has been extensively studied and applied as a simple technique for creating artificial polymer-based recognition gels for a target molecule. Although this technique is effective when targeting small molecules, attempts to extend it to larger templates, such as proteins, have, for the most part, failed to show similar success. Our group has developed a simple simulation model to study protein imprinting. In our previous studies, we investigated the structure of the protein-imprinted pore an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
(68 reference statements)
0
18
0
Order By: Relevance
“…MW (Pang et al ., ; Odabaşi et al ., ; Çimen et al ., ; Pan et al ., ) and IEP (Pan et al ., ; El‐Sharif et al ., ; Zhang et al ., ) have already been suggested as possible explanations for observed PIP selectivity in an ad hoc manner in the literature (Bossi et al ., ; Turner et al ., ; Bossi et al ., ; Chen et al ., ; Uysal et al ., ; Hua et al ., ; Whitcombe et al ., ; Sankarakumar and Tong, ; Li et al ., 2014), and in the succeeding texts, we formalize their effect. Functional group distribution was also suggested as a contributor to protein selectivity (Kimhi and Bianco‐Peled, ; Gai et al ., ; Levi and Srebnik, ; Zayats et al ., ; Lan et al ., ). However, such characterization depends strongly on the method of surface functionality characterization and solution conditions and is beyond the scope of this study [e.g., (Dror et al ., )].…”
Section: Methodsmentioning
confidence: 99%
“…MW (Pang et al ., ; Odabaşi et al ., ; Çimen et al ., ; Pan et al ., ) and IEP (Pan et al ., ; El‐Sharif et al ., ; Zhang et al ., ) have already been suggested as possible explanations for observed PIP selectivity in an ad hoc manner in the literature (Bossi et al ., ; Turner et al ., ; Bossi et al ., ; Chen et al ., ; Uysal et al ., ; Hua et al ., ; Whitcombe et al ., ; Sankarakumar and Tong, ; Li et al ., 2014), and in the succeeding texts, we formalize their effect. Functional group distribution was also suggested as a contributor to protein selectivity (Kimhi and Bianco‐Peled, ; Gai et al ., ; Levi and Srebnik, ; Zayats et al ., ; Lan et al ., ). However, such characterization depends strongly on the method of surface functionality characterization and solution conditions and is beyond the scope of this study [e.g., (Dror et al ., )].…”
Section: Methodsmentioning
confidence: 99%
“…While surface imprinting is an efficient technique to create binding cavities for proteins on the outer layer of MIPNPs with good accessibility and fast rebinding kinetics, the conditions used to accomplish the imprinting process must be carefully considered. The conformational stability of proteins is sensitive to their surrounding conditions, including temperature, pH, ion concentration, surfactant and its concentration, the ratio of template to functional monomers, the types of functional monomers used, and initiator type . Identifying those reaction conditions that ensure the conformational integrity of a template protein and increase binding sites on or near the MIPNP surface, and that ensure good accessibility, are crucial for any useful protein recognition system.…”
Section: Recent Advances In Mipnps For Protein Recognition and Their mentioning
confidence: 99%
“…As recently reviewed, the majority of these studies tend to focus on prepolymerization complexation of the templates and functional monomers, since a correlation between properties of the prepolymerization solution and final imprinting efficiency has been shown to exist . We recently performed lattice Monte Carlo (MC) simulations of the imprinting process using radical polymerization of hydrogels as a simple model for such PIPs . For simplicity, these first studies used a rigid model protein with randomly located functional sites of only 1 type.…”
Section: Introductionmentioning
confidence: 99%
“…The significantly higher IF seen in PIPs over templated gels (where the protein is modeled via excluded volume interactions only) indicated that our model captures the main features of the imprinting process where the pore functionality complements the positioning of functional groups on the template protein surface. Continuation of the study addressed the selectivity of PIP gels against competitor proteins that differ from the template in size, charge densities, or charge distributions . In these models, only short‐ranged forces were used to model interaction between the protein and functional monomers of the gel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation